Figurative Language in Sticks and Stones Standup Comedy by Dave Chappelle - Fauzy, Diki Rizky; Juanda, Juanda; Yuwita, Mia Rahmawati (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
This research analyzes the use of figurative language in Dave Chappelle's standup comedy special